Engineering-Based FE Approach to Appraise Slender Structures Affected by Alkali-Aggregate Reaction (AAR) - Vilela Gorga, Rodrigo (Université d'Ottawa / University of Ottawa, 2018)
Alkali-aggregate reaction (AAR) is one of the most harmful distress mechanisms affecting the performance of aging reinforced concrete structures worldwide. Although several prediction models have been developed to assess the chemical reaction, a thorough and comprehensive approach with the capabilities to correlate important parameters that affect AAR and the mechanical properties of deteriorated materials, as well as the abilities to describe the current damaged state of AAR-affected structures (diagnosis) and predict the potential of further damage (prognosis) is still lacking. Such information is essential in selecting efficient remedial/rehabilitation actions for existing structures in the field. This project aims to develop a practical, yet accurate engineering-based finite element (FE) model for assessing AAR damage and predicting the future behaviour of affected infrastructure. The model is validated through three analyses. First, its capability to accurately simulate sound concrete under mechanical loading is verified by successfully simulating different beam failure mechanisms and cracking patterns, as well as predicting the members’ full force-deflection curves. Next, AAR anisotropic expansion under different stress-state (confinement) conditions is accurately simulated and verified by correlation with laboratory tests. Lastly, an AAR-affected slender reinforced concrete structure (Robert-Bourassa/Charest overpass) is successfully simulated by performing a condition assessment based on several tests performed prior to its demolition.
Keywords: Alkali-aggregate reaction; Concrete; Finite element; Prognosis; Diagnosis